OPTIMALISASI ASESMEN AUTENTIK BERBASIS PJBL BERBANTUAN MADING LINIMASA PANCASILA UNTUK MENILAI UNJUK KERJA SISWA KELAS V SEKOLAH DASAR - Ni Wayan Nik Sri Artini; Dewa Bagus Sanjaya; I Nengah Suastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school students frequently struggle when creating innovative work and presenting ideas. This study aims to evaluate the optimization of Project-Based Learning (PjBL)-based authentic assessment assisted by Pancasila Timeline Bulletin Board media in assessing the performance of fifth-grade students. This performance includes creating a history bulletin board and group oral presentations. Using a descriptive qualitative approach, data were collected through observations, rubrics, and documentation. The results indicated that this authentic assessment effectively reflects students' competence. The synergy between PjBL and authentic assessment creates deep learning in Civic Education and reduces conventional